The Ivory Child - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Ivory Child" by H. Rider Haggard is a novel featuring Allan Quatermain. Two priests from the White Kendah People travel to England seeking Quatermain's help. Their people face annihilation from the Black Kendah, whose evil god inhabits the largest elephant ever seen$1 (Ba beast no man can kill. Quatermain must return to Africa to destroy this supernatural threat before an entire civilization perishes. The novel explores themes of memory loss and fate. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Ivory_Child
Release date is 2006-03-31
John Bickers; Emma Dudding; Dagny; David Widger
Keywords: Fantasy fiction, English; Adventure stories; Quatermain, Allan (Fictitious character) -- Fiction